1999
DOI: 10.1046/j.1440-0960.1999.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific skin lesions occurring in a patient with Hodgkin’s lymphoma

Abstract: A 47-year-old man presented with a several month history of non-specific acquired ichthyosis, an unknown period of generalized lymphadenopathy and a short history of erythematous papules and nodules affecting the cutaneous drainage area of his right axillary lymph nodes. Histology confirmed these lesions to be specific lesions of Hodgkin's lymphoma; that is, metastatic retrograde lymphatic spread from his axillary lymph nodes of CD30+, CD15+, Reed-Sternberg cells as well as mononuclear Hodgkin's cells. This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The typical clinical picture of painless, erythematous papules and nodules that frequently become ulcerated was termed the ''Grosz-Hirschfeld'' type after the physicians who first described it in the early 20th century. [2][3][4][5][7][8][9][10][11] Although specific cutaneous Hodgkin's disease tends to present with distinct lesions, it still must be histologically and immunohistochemically distinguished from infection, graft-versus-host disease, the nonspecific skin conditions that accompany Hodgkin's lymphoma, and other lymphoid proliferations, particularly mycosis fungoides, 12 lymphomatoid papulosis, anaplastic large cell lymphoma, and granulomatous slack skin disease, all of which can be associated with systemic lymphoma. In addition, nonspecific cutaneous manifestations of Hodgkin's disease are common, with between 3% and 50% of patients with Hodgkin's disease experiencing one or more of the following: Addison-like areas of hyperpigmentation, pruritis and associated prurigo, acquired ichthyosis, herpes zoster, and alopecia distinct from that often caused by chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical clinical picture of painless, erythematous papules and nodules that frequently become ulcerated was termed the ''Grosz-Hirschfeld'' type after the physicians who first described it in the early 20th century. [2][3][4][5][7][8][9][10][11] Although specific cutaneous Hodgkin's disease tends to present with distinct lesions, it still must be histologically and immunohistochemically distinguished from infection, graft-versus-host disease, the nonspecific skin conditions that accompany Hodgkin's lymphoma, and other lymphoid proliferations, particularly mycosis fungoides, 12 lymphomatoid papulosis, anaplastic large cell lymphoma, and granulomatous slack skin disease, all of which can be associated with systemic lymphoma. In addition, nonspecific cutaneous manifestations of Hodgkin's disease are common, with between 3% and 50% of patients with Hodgkin's disease experiencing one or more of the following: Addison-like areas of hyperpigmentation, pruritis and associated prurigo, acquired ichthyosis, herpes zoster, and alopecia distinct from that often caused by chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][7][8][9][10][11][12][13][14] The most frequent mode of spread seems to be retrograde from affected nodes, because most of the reported cases occur over areas of skin drained by affected lymph nodes, such as chest and axilla, and pathology does not usually demonstrate direct extension from an adjacent node. 2,[3][4][5] This mode was also likely the case in our patient; his mediastinal nodes were known to have been involved with his lymphoma at one time, and his lesions appeared on his chest.…”
Section: Discussionmentioning
confidence: 99%
“…The epidermis is spared in most of the cases. Few reports documented hyperplasic changes followed by ulceration of the epidermis through the course of the disease 5–8,11–31 …”
Section: Discussionmentioning
confidence: 99%
“…The typical clinical presentation of cutaneous Hodgkin lymphoma represents multiple painless erythematous papulonodules and plaques appearing rapidly in patients with known advanced disease, which become ulcerated through the progression of the disease 5–8,13,14,19,32 . The trunk is the most commonly affected site followed by lower extremities and scalp 7 …”
Section: Discussionmentioning
confidence: 99%
“…In such cases, it was suggested that the appearance of PWSO might represent reactivation that would follow initial spread and sequestration, e.g. in lymph nodes, 3 with subsequent systemic dissemination either through retrograde lymphatic 4 or haematogenous spread into the nail matrix and nail bed. The dermatophyte antigenaemia seen in patients with foot infections would be in keeping with such a mechanism 2 …”
mentioning
confidence: 99%